ISOLASI TOXOPLASMA GONDII PADA AYAM BURAS - Apsari, Ida Ayu Pasti; Artama, Wayan Tunas; -, Sumartono; Damriyasa, I Made; Oka, Ida Bagus Made; Swacita, Ida Bagus Ngurah (Buletin Veteriner Udayana; Vol. 3 No.2 Agustus 2011)
A study was conducted Toxoplasma gondii isolate from the brain and the heart of freerangechickens in Bali. The aim of this study to determine the seroprevalence andto isolate Toxoplasma gondii from free-range chicken heart and brain. To achieve of thisstudy observed 311 free-range chicken serum samples with ELISA method and examined225 free-range chicken brain and heart used digestion method. All of the samples takenfrom 9 districts in Bali. The results showed that the seroprevalence of Toxoplasma gondiiinfreerange chicken has 91.64%. Isolation of Toxoplasma godii from the heart and the brainfreerange chicken found the cyst on inoculate heart and brain, but by bioassay in mice for4 weeks observation failed to find tachyzoite form in peritonial exudat
Keywords: Free-range chicken, digestion method, ELISA, Toxoplasma gondii, bioassay